2023
DOI: 10.5056/jnm22176
|View full text |Cite
|
Sign up to set email alerts
|

Achalasia: The Current Clinical Dilemma and Possible Pathogenesis

Abstract: Achalasia is a primary esophageal motility disorder manifested by dysphagia and chest pain that impair patients' quality of life, and it also leads to chronic esophageal inflammation by food retention and increases the risk of esophageal cancer. Although achalasia has long been reported, the epidemiology, diagnosis and treatment of achalasia are not fully understood. The current clinical dilemma of achalasia is mainly due to its unclear pathogenesis. In this paper, epidemiology, diagnosis treatment, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…This proved that esophageal neurons are the site of VZV infection in achalasia [ 12 ]. At present, the mechanism by which HSV-1 causes achalasia is not fully understood, but there is evidence that achalasia may be an immune-mediated inflammatory disease in which the virus is a trigger [ 56 , 60 62 ]. Facco et al performed flow cytometry analysis of achalasia versus control esophageal tissue and demonstrated that lymphocyte infiltration was significantly elevated in the LES in achalasia and was represented by T cells.…”
Section: Gastrointestinal Dysfunction Due To Viral Infection Of Nervesmentioning
confidence: 99%
“…This proved that esophageal neurons are the site of VZV infection in achalasia [ 12 ]. At present, the mechanism by which HSV-1 causes achalasia is not fully understood, but there is evidence that achalasia may be an immune-mediated inflammatory disease in which the virus is a trigger [ 56 , 60 62 ]. Facco et al performed flow cytometry analysis of achalasia versus control esophageal tissue and demonstrated that lymphocyte infiltration was significantly elevated in the LES in achalasia and was represented by T cells.…”
Section: Gastrointestinal Dysfunction Due To Viral Infection Of Nervesmentioning
confidence: 99%
“…Achalasia and Hirschsprung's disease are known to cause bowel pseudo-obstruction without organic stenosis. Abnormalities in the muscular interlaminar plexus of the intestinal tract may be associated with bowel pseudo- obstruction in both diseases [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we had reasons to believe that the elevation of profilin-1 and transgelin-2 found in this study was caused by achalasia. Previous studies have proposed that achalasia might be an immune-mediated neurodegenerative disease ( 40 , 41 ). The results of using these 2 molecules as biomarkers for achalasia suggested their potential roles in the pathogenesis of achalasia as mediators of either immunological or neurodegenerative processes.…”
Section: Discussionmentioning
confidence: 99%